Thirteen new species, new records, and a new combination on Colombian Myrtaceae - Parra-O., Carlos (Phytotaxa, 2021)
Thirteen new species of Myrtaceae from Colombia are described and illustrated; information about the habitats in which these species are growing, the evaluation of its conservation status, and its affinities are included. Besides, five new records of native and introduced Myrtaceae are reported for Colombia. Also, a new combination of a Myrtaceae species previously described as Calycorectes is proposed here under the genus Eugenia.